Influence of Gd Doping on the Structure and Electrocatalytic Performance of TiO2 Nanotube/SnO2−Sb Nano‐coated Electrode. Issue 22 (21st September 2018) - Yang, Lisha; Zhang, Zhaohan; Liu, Junfeng; Huang, Linlin; Jia, Liu; Feng, Yujie
Abstract: Gd‐doped TiO2 −NT/SnO2 −Sb (NT=nanotube) electrodes were prepared by using a solvothermal synthesis approach with a nano‐sized catalyst coating. Phenol degradation and total organic carbon (TOC) removal followed pseudo‐first‐order kinetics in the experimental range. A maximum rate was achieved by using a Gd doping ratio of 2 % (molar ratio based on Gd/Sn), which was 56.5 % and 68 % higher than that of the control (Gd/0 %) for phenol degradation and TOC removal. The results from the UV scan of the electrolyte showed that introducing an appropriate amount of Gd could promote the electrochemical incineration process, and thus effectively degrade the chemical intermediates during phenol oxidation. In addition, the Gd/2 %‐doped electrode had the longest accelerated life time of 25 h, which was 25 % higher than that of the control. A suitable Gd doping ratio could diminish the SnO2 crystal size and increase the specific surface area, speeding up the electrode's reaction rate, thus promoting the oxygen evolution potential. A regular and compact morphology with a smallest particle size of 9.5 nm was obtained on the Gd/2 %‐doped electrode, which prompted a smaller charge‐transfer resistance and higher electrical double‐layer capacitance than that of the control. The results from X‐ray photoelectron spectroscopy and electron paramagnetic resonance suggested that a maximal of surface active sites (i. e. oxygen vacancy) was formed on the Gd/2 %‐doped electrode, which provided abundant positive charge for adsorbing more oxygen species (37.5 %) than the control (21.5 %), and greatly enhanced the formation of ·OH to attack the targeted pollutant. Abstract : Targeting pollutants : Electrocatalytic oxidation of organic pollutants on the Gd‐doped TiO2 nanotube/SnO2 −Sb nano‐coated anode (see picture).